2018
DOI: 10.1371/journal.pone.0190423
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the experience and manifestation of depression in adolescents living with HIV in Harare, Zimbabwe

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 26 publications
4
64
0
1
Order By: Relevance
“…Links between poor mental health and suicide are well established, including among adolescents (Wild et al, 2004). Adolescence is a high risk period for the development of mental health problems (Kessler et al, 2012) and there is evidence to suggest that ALHIV may be at elevated risk of mental health disorders (Scharko, 2006;Mellins and Malee, 2013;Willis et al, 2018). Moreover, several Southern African studies, including longitudinal analyses, have shown poor mental health to mediate the relationship between specific stressors, such as parental death and abuse, and suicidal thoughts and behaviours among adolescents (Cluver et al, 2015;Shilubane et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Links between poor mental health and suicide are well established, including among adolescents (Wild et al, 2004). Adolescence is a high risk period for the development of mental health problems (Kessler et al, 2012) and there is evidence to suggest that ALHIV may be at elevated risk of mental health disorders (Scharko, 2006;Mellins and Malee, 2013;Willis et al, 2018). Moreover, several Southern African studies, including longitudinal analyses, have shown poor mental health to mediate the relationship between specific stressors, such as parental death and abuse, and suicidal thoughts and behaviours among adolescents (Cluver et al, 2015;Shilubane et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It emerged that YPLHIV experience significant psychological challenges including anxiety, worry, and stigma which, if not addressed, often lead to self-isolation and avoidance of proactive behaviors [39]. Support from friends, family and intimate partners was frequently mentioned as a strategy of counteracting the psychosocial challenges experienced by YPLHIV.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in sub-Saharan Africa have described NCD comorbidities in adults living with HIV [44,[109][110][111][112]. Besides mental health [113][114][115][116][117][118][119][120][121] and lung diseases [122][123][124][125][126], few studies have assessed the prevalence of NCDs and particularly NCD risk factors in AYLHIV in SSA other than as incidental ndings [127][128][129][130][131][132][133][134]. Risk behaviour research on AYLHIV in sub-Saharan Africa has predominantly focused on sexual risk behaviour [135].…”
Section: Discussionmentioning
confidence: 99%